The Contribution of Learning Motivation and Learning Styles to Numeracy Literacy Skills: A Regression-Based Study - Susetyawati, M.M. Endang; Warniasih, Kristina; Ernawati, Ika (The Indonesian Institute of Science and Technology Research, 2025)
This study aims to examine the effect of learning motivation and learning styles on the numeracy literacy skills of grade 7 at SMP Negeri 2 Kasihan. The research employed a quantitative approach with an ex post facto design. The sample consisted of 120 students selected purposively, and the study was conducted from February to May 2025. The research instruments included a learning motivation questionnaire, a learning style questionnaire, and a numeracy literacy test, all of which underwent construction, expert validation, and pilot testing. Most of the items were found to be valid and reliable, except for several items in the numeracy literacy test that were eliminated. The data were analyzed using descriptive statistics to obtain the maximum, minimum, total, and mean scores for each variable. The prerequisite tests included normality, multicollinearity, heteroscedasticity, and linearity, all of which indicated that the data met the assumptions for regression analysis. The results of multiple linear regression analysis revealed that learning motivation and learning styles simultaneously had a significant effect on numeracy literacy skills (sig. 0.000 < 0.05). However, partially, neither learning motivation nor learning styles showed a significant effect. The coefficient of determination (R²) of 0.276 indicates that the two independent variables explained 27.6% of the variance in students’ numeracy literacy skills, while the remaining variance was influenced by other factors beyond this study.